SAPHO Syndrome with Palmoplantar Pustulosis as the First Manifestation Successfully Treated with Adalimumab - Yang Q; Xiang T; Wu Y; Ye E; He B; Bu Z (Dove Medical Press, 2022)
Qingyun Yang,1,* Tingkai Xiang,1,* Yangfan Wu,1,* Enyi Ye,1,* Beilei He,1,* Zhangyu Bu2,* 1Department of The Fourth School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310006 People's Republic of China; 2Department of Dermatology, Affiliated Hangzhou First People's Hospital, Zhejiang University School of Medicine, Hangzhou, 310006, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhangyu Bu, Department of The Fourth School of Clinical Medicine, Zhejiang University School of Medicine, No. 261, Huansha Road, Hangzhou, Zhejiang, 310006, People's Republic of China, Fax +8657156006617, Email buzyhz@163.comIntroduction: Synovitis-acne-pustulosis-hyperostosis-osteitis (SAPHO) syndrome is an acronym for synovitis, pustulosis, acne, hyperostosis, and osteitis, and clinically manifests as dermatological and musculoskeletal damage. Two major manifestations that co-occur in a single patient are rare.Methods/Results: This literature describes a 44-year-old male affected by SAPHO syndrome, whose first manifestation was palmoplantar pustulosis (PPP). Symptomatic treatments such as anti-inflammatory and analgesics did not work well for him. Adalimumab provided noteworthy improvement in the neck and thoracic back pain improvement after two weeks. The palmoplantar pustules were alleviated after four weeks.Conclusion: The literature on SAPHO syndrome therapy is increasing. Thus, adalimumab is a novel therapeutic agent. This report demonstrates the efficiency of adalimumab in SAPHO syndrome.Keywords: synovitis, acne, psoriasis, bone hypertrophy, osteitis, psoriasis arthritis, adalimumab